2016
DOI: 10.1186/s12959-016-0106-0
|View full text |Cite
|
Sign up to set email alerts
|

Current animal models of hemophilia: the state of the art

Abstract: Hemophilia is the most well-known hereditary bleeding disorder, with an incidence of one in every 5000 to 30,000 males worldwide. The disease is treated by infusion of protein products on demand and as prophylaxis. Although these therapies have been very successful, some challenging and unresolved tasks remain, such as reducing bleeding rates, presence of target joints and/or established joint damage, eliminating the development of inhibitors, and increasing the success rate of immune-tolerance induction (ITI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…Available preclinical animal models for HA (rats, dogs, sheep, and genetically engineered mice and pigs) are all centered around developing appropriate therapies for HA [8]. Only recently, we have shown that miRNAs can influence the HA disease outcomes, including in patients with the normal F8 gene [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Available preclinical animal models for HA (rats, dogs, sheep, and genetically engineered mice and pigs) are all centered around developing appropriate therapies for HA [8]. Only recently, we have shown that miRNAs can influence the HA disease outcomes, including in patients with the normal F8 gene [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Several preclinical animal models of HA are presently available which can be used for the development of new gene therapy strategies to treat HA, to evaluate safety, as well as for dosage and long-term follow-up studies. These models include HA animals with spontaneous mutations, such as dogs, sheep and rats, and genetically engineered animals, like mice and pigs (59). Moreover, the generation of a HA mouse model carrying the human HLA class II antigen, associated in humans with higher inhibitor development risk, has given us the possibility to better understand/characterize mechanisms involved in immune reaction against FVIII (20,60).…”
Section: Gene Therapymentioning
confidence: 99%
“…In this study, 48 patients with a medical history of clotting factor treatment for large joint bleeds were compared to a matched control group of 48 patients who did not receive treatment for joint bleeds. 6 During the study visit, all these participants were questioned on the occurrence, frequency…”
Section: Me Thodsmentioning
confidence: 99%
“…These well-characterized models have been extensively employed to evaluate new treatments. 6 In this report, we have studied the progression of chemically induced liver fibrosis by means of an haemophilia A mouse model.…”
mentioning
confidence: 99%